Phase transformation and subsurface damage formation in the ultrafine machining process of a diamond substrate through atomistic simulation - Van-Thuc Nguyen (Nature Portfolio, 2021)
Abstract This report explores the effects of machining depth, velocity, temperature, multi-machining, and grain size on the tribological properties of a diamond substrate. The results show that the appearance of graphite atoms can assist the machining process as it reduces the force. Moreover, the number of graphite atoms relies on the machining speed and substrate temperature improvement caused by the friction force. Besides, machining in a machined surface for multi-time is affected by its rough, amorphous, and deformed surface. Therefore, machining in the vertical direction for multi-time leads to a higher rate of deformation but a reduction in the rate of graphite atoms generation. Increasing the grain size could produce a larger graphite cluster, a higher elastic recovery rate, and a higher temperature but a lower force and pile-up height. Because the existence of the grain boundaries hinders the force transformation process, and the reduction in the grain size can soften the diamond substrate material.